Assessment for Quality of Life in Cities Taking into Account Ecological and Energy Factors - BELIK, Irina; STARODUBETS, Natalia; ALIKBEROVA, Tamila (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017, 2017)
The paper is devoted to the problem of improving the methodology for assessing the quality of life in cities by including ecological and energy factors. The authors carried out an analytical assessment of existing methods of evaluating the quality of life and proved the need to take into account ecological and energy factors. Suggestions were made in the paper to improve the methodology of the Council for study of productive forces and incorporate indicators that characterize the environmental and energy components of the integrated quality of life indicator. Approbation was carried out on Sverdlovsk region and the city of Ekaterinburg. The obtained results can be used for planning and forecasting socio-economic development of regions and cities, as well as in the development of concrete measures for improving social and environmental policies.